Audit Tenure, CEO Educational Background, and Governance Effectiveness: An Empirical Investigation of Financial Statement Fraud - Umi Nur Fryda Kusli Rochmah; Gideon Setyo Budiwitjaksono (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the influence of audit tenure, CEO education, and ineffective monitoring on fraudulent financial statements in state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange during the period 2021–2023. A quantitative approach is employed, utilizing panel data regression analysis on a sample of 19 BUMN companies. Data were obtained from annual report documentation and analyzed using E-Views 12 software. Fraudulent financial reporting is measured using the Beneish M-Score as a proxy. The results reveal that audit tenure and ineffective monitoring do not have a statistically significant effect on the likelihood of financial statement fraud. In contrast, CEO education has a significant negative effect, suggesting that higher levels of CEO education are associated with a lower propensity for fraudulent financial reporting. Furthermore, when assessed simultaneously, the three variables collectively exhibit a significant influence on the occurrence of fraudulent financial statements. These findings underscore the important role of CEO educational attainment in enhancing financial reporting integrity and preventing fraudulent practices.